Hydrological dynamics and fire history of the last 1300 years in western Siberia reconstructed from a high-resolution, ombrotrophic peat archive. Issue 3 (November 2015) - Lamentowicz, Mariusz; Słowiński, Michał; Marcisz, Katarzyna; Zielińska, Małgorzata; Kaliszan, Karolina; Lapshina, Elena; Gilbert, Daniel; Buttler, Alexandre; Fiałkiewicz-Kozieł, Barbara; Jassey, Vincent E.J.; Laggoun-Defarge, Fatima; Kołaczek, Piotr
Abstract : Siberian peatlands provide records of past changes in the continental climate of Eurasia. We analyzed a core from Mukhrino mire in western Siberia to reconstruct environmental change in this region over the last 1300 years. The pollen analysis revealed little variation of local pine-birch forests. A testate amoebae transfer function was used to generate a quantitative water-table reconstruction; pollen, plant macrofossils, and charcoal were analyzed to reconstruct changes in vegetation and fire activity. The study revealed that Mukhrino mire was wet until the Little Ice Age (LIA), when drought was recorded. Dry conditions during the LIA are consistent with other studies from central and eastern Europe, and with the pattern of carbon accumulation across the Northern Hemisphere. A significant increase in fire activity between ca. AD 1975 and 1990 may be associated with the development of the nearby city of Khanty-Mansiysk, as well as with the prevailing positive Arctic Oscillation.